2010
DOI: 10.1369/jhc.2010.956565
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FAM20C in the Osteogenesis and Odontogenesis of Mouse

Abstract: S U M M A R Y Mutations in FAM20C were recently identified as the cause of lethal osteosclerotic bone dysplasia, which highlighted the important role of this molecule in biomineralization. No systematic studies have been performed to evaluate the expression pattern of this relatively new molecule in the developmental processes of bone and tooth. In the present study, we analyzed in detail the expression profile of FAM20C during osteogenesis and odontogenesis using ISH and IHC approaches. The specimens analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 13 publications
2
77
0
Order By: Relevance
“…The periosteal proliferation and lysis of tooth roots, cementum, and periodontal bone were mostly due the periapical inflammation and necrosis extending from the pulp cavity, although a role for primary defects in these locations cannot be ruled out given the reported expression of FAM20C in ameloblasts, odontoblasts, cementoblasts, and periodontal ligament fibroblasts. 108 The markedly thickened maxillae and mandibles were a prominent feature in Fam20c -/-mice and mirrored similar changes in other bones throughout the body, where trabeculae were outlined by broad bands of osteoid.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The periosteal proliferation and lysis of tooth roots, cementum, and periodontal bone were mostly due the periapical inflammation and necrosis extending from the pulp cavity, although a role for primary defects in these locations cannot be ruled out given the reported expression of FAM20C in ameloblasts, odontoblasts, cementoblasts, and periodontal ligament fibroblasts. 108 The markedly thickened maxillae and mandibles were a prominent feature in Fam20c -/-mice and mirrored similar changes in other bones throughout the body, where trabeculae were outlined by broad bands of osteoid.…”
Section: Discussionmentioning
confidence: 78%
“…86 The localization of FAM20C in the matrices of dentin, enamel, and alveolar bone suggests that it is an extracellular matrix protein. 108 Mutations in FAM20C have been linked to Raine syndrome in humans, an osteosclerotic bone dysplasia, proving a role for FAM20C protein in bone development and mineralization. 36, 86 Raine syndrome is accompanied by increased periosteal bone formation and facial dysmorphism.…”
mentioning
confidence: 99%
“…Biochemical analysis of the patients' sera identified elevated intact FGF23. Because FGF23 is expressed in tissues that show high levels of Fam20C expression (30) and contains Fam20C consensus S-x-E/pS motifs (Fig. 1A), we hypothesized that Fam20C may directly regulate FGF23 by phosphorylation.…”
Section: Fgf23mentioning
confidence: 99%
“…Thus, interruption of the signaling in one tissue may cause abnormalities in the other. Analysis of our previous data indicated that FAM20C is expressed in both ameloblasts and odontoblasts (Wang et al 2010);Sox2-Cre;Fam20C fl/fl mice, in which Fam20C was ubiquitously inactivated, had both dentin and enamel defects, as well as hypophosphatemic rickets. It remains to be determined if the enamel and dentin defects in the Fam20C-cKO mice are correlated with, or independent of, each other, and if hypophosphatemia contributes to the dental defects, since phosphate composes the major content of hydroxylapatite in both dentin and enamel.…”
Section: Introductionmentioning
confidence: 97%